Public affairs : politics in the age of sex scandals - Apostolidis, Paul, 1965-; Williams, Juliet (e-Duke books scholarly collection., 2004)
Collection of essays analyzing political sex scandals and U.S. political culture from a variety of theoretical angles, including feminism, cultural studies, Marxist critical theory, queer theory, and critical race theory.